HUBUNGAN TASK COMMITMENT DAN EDUCATIONAL INTERACTION DENGAN PRESTASI BELAJAR MAHASISWA DEPARTEMEN PENDIDIKAN GEOGRAFI FKIP UNIVERSITAS SYIAH KUALA - Fithri, Salsabiila; Abdi, Abdul Wahab; Jummi, Cut Vita Rajiatul (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2024)
Academic achievement is one of the indicators of student success. Good academic performance is expected to reflect high student quality, especially for prospective teachers who must educate future generations. Task commitment is an internal factor, while educational interaction is an external factor that can influence student academic achievement. The research problem in this study is how task commitment and educational interaction relate to the academic achievement of Geography Education students at FKIP, Syiah Kuala University. This study aims to determine the relationship between task commitment and educational interaction with student academic achievement. A quantitative correlational approach was used in this research. The population consisted of 346 active students in the Geography Education Department, with a sample of 77 students selected using proportional random sampling. Data were collected through documentation and questionnaires. The data analysis techniques used were multiple correlation and significance tests. The results showed a multiple regression equation of Y = 15.97 + 0.73X + 0.15X, indicating that both independent variables positively influence the dependent variable. The correlation coefficient between task commitment and educational interaction with academic achievement was 0.80, categorized as very strong, with a coefficient of determination of 64%. The significance test results showed Fcount (66.7) Ftable (3.12) at a 5% significance level, leading to the rejection of H. This means there is a significant relationship between task commitment and educational interaction with the academic achievement of Geography Education students at FKIP, Universitas Syiah Kuala.